Gastropods on Marine Debris at Mangrove Ecosystem - Prasetiawan, Nanda Radhitia; Kurniasih, Ratna Amalia; Damayanti, Putri Milenia; Agus, Muhammad (UIN Sunan Gunung Djati Bandung, 2023)
The mangrove ecosystem is one of the accumulation areas for various marine debris including plastic and also the habitat for gastropods. This condition allows direct contact between gastropods and debris which can be an entranceway for contamination in biota. This study aimed to know the species of gastropods in the marine debris in the Bulaksetra mangrove ecosystem in Pangandaran. The method used was stratified random sampling with a transect line of 100 m. Gastropods and debris in the 1 m x 1 m square in the 10 m x 10 m plot were collected, identified, counted, and determined in composition. There were 22 types of marine debris in the Bulaksetra mangrove ecosystem which were dominated by plastic. 16 species of gastropods were found in the area around the debris and 15 species were found attached to the debris. Gastropods can be found on the top, middle, or bottom surfaces of plastic waste. Faunus ater and Terebralia palustris dominate in the surrounding area and the debris. Treefauna gastropods utilize stuck debris to move from one part to another part of the tree. Plastic waste has become part of the mangrove habitat and there are interactions with gastropods that use it as a living medium.